Analisis Yuridis Praktik Manipulasi Pasar oleh Influencer Saham dan Dampaknya Terhadap Investor Ritel (Studi Kasus Otoritas Jasa Keuangan terhadap Influencer BVN) - Rawia Salsabilla; Faizal Muslim; Sahara Intan Sari; Ananda Nabila Pasya; Sunarko Sunarko; Emiel Salim Siregar (KOLONI, 2026)
The development of technology and social media has encouraged the emergence of the stock influencer phenomenon (finfluencer) which has a significant influence of investment decisions, especially for retail investors, which on the one hand increases financial literacy but on the other hand has the potential to cause market manipulation practices. This research aims to analyze the legal regulations of market manipulation, examine the forms and modes of practice carried out by stock influencers, asses legal responsibility of retail investor losses, and examine the role of the Otoritas Jasa Keuangan as finansial services authority in law enforcement and investor protection. The research method used is normative jurisdical with a legislative approach and a case approach to BVN influencer cases. The research results show that the practice of market manipulation has been regulated in the Capital Market Act, but the regulation still general and has not yet accomodated the finfluencer phenomenon, with the mode of spreading stock recommendations through social media, utilizing influence on retail investors, using multiple securities accounts, and the practice of pump and dump. This research concludes that stock influencers can be held accountable administratively, civilly, and criminally, as well as affirming the importance of strengthening the role of regulators in dealing with capital market dynamics in the digital era.